Detection of Herpes Simplex and Varicella-Zoster Virus in Clinical Specimens by Multiplex Real-Time PCR and Melting Curve Analysis. (16th April 2014) - Hong, Yun Ji; Lim, Mi Suk; Hwang, Sang Mee; Kim, Taek Soo; Park, Kyoung Un; Song, Junghan; Kim, Eui Chong
Abstract : Herpes simplex viruses types 1 and 2 (HSV-1 and HSV-2), and varicella-zoster virus (VZV) are common agents resulting in various forms of clinical manifestation from skin vesicle to disseminated viral infection. The aim of the present study was to develop a real-time PCR and melting curve analysis which detect and differentiate HSV-1, HSV-2, and VZV, to compare with PCR-RFLP using clinical specimens, and to introduce the 4-year experience in the clinical laboratory. Three pairs of primers for HSV-1, HSV-2, and VZV were designed. Primers for human endogenous retrovirus-3 (HERV-3), an internal control, were adopted. A hundred selected specimens and many clinical specimens were tested for methods comparison and assay validation. Increased sensitivity and specificity were obtained from real-time PCR. In review of results of clinical specimens submitted to clinical laboratory, a total of 46 of 3, 513 specimens were positive in cerebrospinal fluids, blood, skin vesicles, genital swabs, aqueous humor, and ear discharge. Thus, this method could be a rapid and accurate alternative to virus culture and other molecular tests for detection and typing of HSV-1, HSV-2, and VZV.